A Review on Biomedical Waste Management - Shridhar Shrimant Bagali; Bychapur Siddaiah Gowrishankar; Sachin Shrimant Bagali (Waste Technology, 2021)
With the growth of healthcare facilities, the amount of biomedical waste produced every day is growing. If biomedical waste management is done correctly, many of the problems can be avoided. Segregation, storage, processing, transportation, and disposal of biomedical waste are all common practices undertaken as part of health care waste management. It involves interdisciplinary relationships in organizational, planning, administrative, financial, engineering, legal, and human resource creation. Medical waste management necessitates dedication from healthcare providers at all levels. The risks and value of their "contribution" are feared in a system run by reckless and untrained personnel. Also trained medical professionals, such as hospital managers, private and governmental institutes, clinics, and universities, need to be taught about the rules for disposing of biomedical waste. The importance of biomedical waste, its interaction with the ecosystem, the environmental pollutants used in the health care industry, and the effect of callousness on public health are all topics that are still largely unknown. To achieve better results, we must raise the level of training and education in biomedical waste and environmentally sustainable health care as quickly as possible, while adhering to all applicable rules and regulations.